Haptic Interfaces for Virtual Reality: Challenges and Research Directions - Wee, Chyanna*; Yap, Kian Meng *; Lim, Woan Ning * (Institute of Electrical and Electronics Engineers, 2021)
The sense of touch (haptics) has been applied in several areas such as tele-haptics, telemedicine, training, education, and entertainment. As of today, haptics is used and explored by researchers in many more multi-disciplinary and inter-disciplinary areas. The utilization of haptics is also enhanced with other forms of media such as audio, video, and even sense of smell. For example, the use of haptics is prevalent in virtual reality environments to increase the immersive experience for users. However, while there has been significant progress within haptic interfaces throughout the years, there are still many challenges that limit their development. This review highlights haptic interfaces for virtual reality ranging from wearables, handhelds, encountered-type devices, and props, to mid-air approaches. We discuss and summarize these approaches, along with interaction domains such as skin receptors, object properties, and force. This is in order to arrive at design challenges for each interface, along with existing research gaps.